"Play with Me, Darling!" Testing the Associations between Adult Playfulness and Indicators of Sexuality. Issue 4 (4th May 2023) - Brauer, Kay; Friedemann, Stanley F.; Chick, Garry; Proyer, René T.
ABSTRACT: Previous studies have shown that individual differences in adult playfulness are important in interpersonal relationships. However, there is a lack of research on the role of playfulness in human sexuality. Using three studies with four independently collected samples ( N total  = 1, 124) we tested the differential relations between global playfulness and four facets of playfulness (O ther-directed, L ighthearted, I ntellectual, W himsical; OLIW) with broad ("Sexy Seven") and narrow (sociosexuality, sexual sensation seeking, and sexual compulsivity) sexuality-related personality traits and sadomasochistic sexual practices (BDSM). Our main findings were: (1) Each of the Sexy Seven traits was related to global playfulness or at least one playfulness facet while only Whimsical playfulness (liking odd and/or unusual things, persons, or activities) was related to each Sexy Seven trait; (2) Sexual sensation seeking related to playfulness with small effect sizes ( f 2  ≤ 0.11), Whimsical playfulness positively related to narrow traits of sexuality; and (3) those engaging in BDSM were more playful than non-practitioners. The findings support the notion that playfulness (particularly Whimsical playfulness) relates to sexuality-related personality traits and sadomasochistic practices may be one way of expressing adult playfulness.